A panel of recombinant proteins for the serodiagnosis of caseous lymphadenitis in goats and sheep - Barral, Thiago Doria; Mariutti, Ricardo Barros [UNESP]; Arni, Raghuvir Krishnaswamy [UNESP]; Santos, Anderson Jesus; Loureiro, Dan; Sokolonski, Ana Rita; Azevedo, Vasco; Borsuk, Sibele; Meyer, Roberto; Portela, Ricardo Dias (Wiley, 2019)
Caseous lymphadenitis (CLA) is a small ruminant disease characterized by the development of granulomatous lesions in superficial and internal lymph nodes, as well as in some organs, and causes significant economic losses worldwide. The aetiological agent of CLA is the bacterium Corynebacterium pseudotuberculosis; however, the commercially available diagnostic tools present problems with regard to specificity, which can lead to false-negative results. This study aimed to develop an indirect enzyme-linked immunosorbent assay (ELISA) for the detection of specific immunoglobulins in goats and sheep using recombinant C. pseudotuberculosis PLD, CP40, PknG, DtxR and Grx proteins. For validation of the ELISAs, 130 goat serum samples and 160 sheep serum samples were used. The best ELISA for goats was developed using a combination of PLD and CP40 as antigens at a 1:1 ratio, which presented 96.9% sensitivity and 98.4% specificity. The most effective ELISA for sheep presented 91% sensitivity and 98.7% specificity when recombinant PLD alone was used as the antigen. These ELISAs can be used as highly accurate tools in epidemiological surveys and for the serodiagnosis of C. pseudotuberculosis infection in goats and sheep.